A 3‐week nonalcoholic steatohepatitis mouse model shows elafibranor benefits on hepatic inflammation and cell death. Issue 3 (25th January 2020) - Briand, François; Heymes, Christophe; Bonada, Lucile; Angles, Thibault; Charpentier, Julie; Branchereau, Maxime; Brousseau, Emmanuel; Quinsat, Marjolaine; Fazilleau, Nicolas; Burcelin, Rémy; Sulpice, Thierry
Abstract : The long duration of animal models represents a clear limitation to quickly evaluate the efficacy of drugs targeting nonalcoholic steatohepatitis (NASH). We, therefore, developed a rapid mouse model of liver inflammation (i.e., the mouse fed a high‐fat/high‐cholesterol diet, where cyclodextrin is co‐administered to favor hepatic cholesterol loading, liver inflammation, and NASH within 3 weeks), and evaluated the effects of the dual peroxisome proliferator‐activated receptor alpha/delta agonist elafibranor (ELA). C57BL6/J mice were fed a 60% high‐fat, 1.25% cholesterol, and 0.5% cholic acid diet with 2% cyclodextrin in drinking water (HFCC/CDX diet) for 3 weeks. After 1 week of the diet, mice were treated orally with vehicle or ELA 20 mg/kg q.d. for 2 weeks. Compared with vehicle, ELA markedly reduced liver lipids and nonalcoholic fatty liver disease activity scoring, through steatosis, inflammation, and fibrosis (all P  < 0.01 vs. vehicle). Flow cytometry analysis showed that ELA significantly improved the HFCC/CDX diet‐induced liver inflammation by preventing the increase in total number of immune cells (CD45+), Kupffer cells, dendritic cells, and monocytes population, as well as the reduction in natural killer and natural killer T cells, and by blocking conversion of T cells in regulatory T cells. ELA did not alter pyroptosis (Gasdermin D), but significantly reduced necroptosis (cleaved RIP3) and apoptosis (cleaved caspase 3) in the liver. In conclusion, ELA showed strong benefits on NASH, including improvement in hepatic inflammation, necroptosis, and apoptosis in the 3‐week NASH mouse. This preclinical model will be useful to rapidly detect the effects of novel drugs targeting NASH.